Persepsi pustakawan atas aspek hubungan pesan dalam transaksi referensi Tanya Pustakawan Chat Perpusnas - Arief Wicaksono (Perpustakaan Universitas Gadjah Mada, 2024)
Introduction. This paper investigates librarians' perception towards relationships in reference transaction in the context of Ask Librarian at National Library of Indonesia. Aspects dicussed within the relationships include opening and closing ritual, rapport building, and compensation for lack of nonverbal cues. The paper was written using Radford's concept. Data Collection Methods. The paper used a quantitative approach with descriptive statistics. Data Analysis. The quantitativa data were converted to qualitative data as an importance index to show the average. Results and Discussion. Perceptions of the content and relationship aspects are very important. The importance index of the relationship aspect showed significant. Besides, the index of opening ritual, building relationships, and closing rituals also important. The index of compensation for the lack of nonverbal cues showed less important. Conclusion. The content and relationship aspects are perceived as very important. Relational facilitators are also perceived as important. Compensation for nonverbal cues and humor are perceived as less important. The Radford's concept can be applied in the context of librarians' perceptions of chat reference services in the context of national library in Indonesia. Further research may discuss their topic from the perspectives of content analysis of chat transcripts and users survey.